Exosomes as a Source of Cancer Biomarkers: Advances in Electrochemical Biosensing of Exosomes. Issue 9 (10th March 2020) - Lorencova, Lenka; Bertok, Tomas; Bertokova, Aniko; Gajdosova, Veronika; Hroncekova, Stefania; Vikartovska, Alica; Kasak, Peter; Tkac, Jan
Abstract: Exosomes are naturally produced biological nanoparticles secreted by cells into body fluids and responsible for intercellular communication. Exosomes can also carry cargo affecting neighbouring cells and forming pre‐metastatic niches. Hence, exosomes are behind localised tumour development, progression, but also the induction of distant tumours forming metastasis. A substantially higher cellular activity of tumour cells results in the production of a greater number of exosomes than in normal, healthy cells. Therefore, the number of exosomes present in body fluids can serve as a good diagnostic biomarker in itself, besides the presence of other tumour biomarkers, which can be substantially enriched in exosomes compared to parental cells. This review comprehensively summarises the development of electrochemical biosensors for the detection of exosome levels, exosome‐derived cancer biomarkers in cell lines and serum samples for the better diagnosis of various cancer types. The review provides information on the design and analytical parameters of such biosensors. The clinical utility of the level of exosomes or exosome‐derived biomarkers is also provided. Abstract : Cancer diagnostics : Different configurations, approaches, and electrochemical methods to detect and analyze exosomes (tumor biomarkers) and/or their composition are summarized in this review.